2017
DOI: 10.4103/sni.sni_479_16
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 30-day mortality in spontaneous cerebellar hemorrhage

Abstract: Background:Cerebellar hemorrhage is a potentially life-threatening condition and an understanding of the factors influencing outcome is essential for sound clinical decision-making.Methods:We retrospectively evaluated data from 50 consecutive patients who suffered a first spontaneous cerebellar hemorrhage (SCH) from 2005 to 2014, analysing their short-term outcomes and identifying possible clinical, radiological and therapeutic risk factors for poor prognosis and death within 30 days.Results:Among 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Spontaneous cerebellar hemorrhage (SCH) account for represent 5 to 13% of all cases of spontaneous intracerebral hemorrhage and about 15% of cerebellar strokes [16]. It is often due to hypertension and the reported mortality rate within 6 months can reach 50%, and more than 60% of surviving patients had moderate or severe disability [68]. The prognostic risk factors of outcome in patients with SCH including hyperglycemia and platelet count at admission, a larger hematoma volumes or diameter, a lower Glasgow Coma Scale (GCS) at admission, and imaging findings that reveal the initial presence of hydrocephalus, intraventricular hemorrhage (IVH), the appearance of the fourth ventricle, or basal cistern obliteration have been reported in several studies [2, 6, 812].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous cerebellar hemorrhage (SCH) account for represent 5 to 13% of all cases of spontaneous intracerebral hemorrhage and about 15% of cerebellar strokes [16]. It is often due to hypertension and the reported mortality rate within 6 months can reach 50%, and more than 60% of surviving patients had moderate or severe disability [68]. The prognostic risk factors of outcome in patients with SCH including hyperglycemia and platelet count at admission, a larger hematoma volumes or diameter, a lower Glasgow Coma Scale (GCS) at admission, and imaging findings that reveal the initial presence of hydrocephalus, intraventricular hemorrhage (IVH), the appearance of the fourth ventricle, or basal cistern obliteration have been reported in several studies [2, 6, 812].…”
Section: Introductionmentioning
confidence: 99%
“…Of these 121 articles, 41 (34%) articles fulfilled the predefined inclusion criteria and were therefore included in this systematic review (figure 1). 4 12–51 The 41 eligible studies described 2062 patients (40% female) of which 1171 (57%) underwent haematoma evacuation and 891 (43%) did not. Thirty-seven (90%) studies had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the available literature and its limitations as described previously, there is currently insufficient published evidence to guide treatment decisions on when and for whom haematoma evacuation for spontaneous cerebellar ICH should be performed 13–51. Ultimately, randomised clinical trials may well be needed to assess the role of haematoma evacuation in patients with spontaneous cerebellar ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Al Safatli D showed that a GCS score <10 on admission was associated with increased 30-day mortality and poorer short-term outcomes of patients with SCH. 34 Other researchers have demonstrated that GCS scores ≤ 8 on arrival are a strong predictive factor for first-week mortality and shortand long-term poor prognoses of patients with SCH. [35][36][37][38] Hydrocephalus was observed in 22.6% of all patients, similar to the previously reported 23%.…”
Section: Discussionmentioning
confidence: 97%